Industry Perspectives on Market Access of Innovative Drugs: The Relevance for Oncology Drugs - Pauwels, Kim (Front Pharmacol, 2016)
Key Points: - Representatives of the pharmaceutical industry call for a broader recognition of value within the assessment and appraisal of innovative drugs; - Focus on value within the assessment and appraisal of drugs is jeopardized by financial drives as the side of industry and at the side of the payers; - A well–considered value-framework, with attention for patient reported outcomes, societal preferences and dynamic approach on the drug life cycle, needs to be incorporated in assessment and appraisal at national and European level in order to coordinate the views of different stakeholders and allow efficient resource allocation. This study presents industry perspectives on the challenges related to market access of innovative drugs in general and oncology drugs in specific. Fifteen interviews were conducted with representatives of pharmaceutical companies and industry associations. Interviewees call for a broader recognition of value within the assessment and appraisal of drugs. According to interviewees, focus on value is jeopardized by the lack of a common value definition across Europe, poor availability and validity of value measures and cost-saving measures such as external reference price setting and cost-effectiveness analysis at the side of the payers. Centralized assessment of relative-effectiveness at European level would provide a common value estimate across member states, independent of financial drivers. Empirical evidence on PRO and societal preferences is however essential in the development of a value definition. Furthermore, value-based pricing would imply a dynamic approach where the price is differentiated across indications and across the lifecycle of the drug, especially in fields such as oncology. Financial drivers however also threat the application of value-based pricing at the side of the industry, making value-based profitability a more appropriate term.